Notes on Inquisition and Femininity in Hispanic Culture - Torquemada Sánchez, Mª Jesús (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2012)
This study involves examining some aspects concerning the social impact the establishment of the inquisitorial Hispanic courts had at that time. This is based on the legal approaches that cannot be silenced when we refer to an institution that was created to administer justice on the basis of only partly religious criteria. In fact, the Spanish Inquisition sought to safeguard a particular social order, while intending to maintain Catholic orthodoxy in all territories of the Monarchy. Within this context, all aspects that define a person as a member of the Hispanic world are important when setting the inquisitorial machine in motion. The distinction of the subjects on the basis of their sex is seen as one of the variables that made a difference when the rules created or assumed by the Holy Office were to be applied.
Keywords: Inquisition; women; New World; America; trial; torture; witchcraft; bigamy.